Biomechanical evaluation of a novel intervertebral disc repair technique for large box-shaped ruptures - Nie, Mao-Dan; Huang, Ze-Bin; Zhang, Ning-Ze; Fu, Ling-Jie; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: The purpose of this study was to analyze the feasibility of repairing a ruptured intervertebral disc using a patch secured to the inner surface of the annulus fibrosus (AF). Different material properties and geometries for the patch were evaluated. Methods: Using finite element analysis, this study created a large box-shaped rupture in the posterior-lateral region of the AF and then repaired it with a circular and square inner patch. The elastic modulus of the patches ranged from 1-50 MPa to determine the effect on the nucleus pulposus (NP) pressure, vertical displacement, disc bulge, AF stress, segmental range of motion (ROM), patch stress, and suture stress. The results were compared against the intact spine to determine the most suitable shape and properties for the repair patch. Results: The intervertebral height and ROM of the repaired lumbar spine was similar to the intact spine and was independent of the patch material properties and geometry. The patches with a modulus of 2-3 MPa resulted in an NP pressure and AF stresses closest to the healthy disc, and produced minimal contact pressure on the cleft surfaces and minimal stress on the suture and patch of all models. Circular patches caused lower NP pressure, AF stress and patch stress than the square patch, but also caused greater stress on the suture. Conclusion: A circular patch with an elastic modulus of 2-3 MPa secured to the inner region of the ruptured annulus fibrosus was able to immediately close the rupture and maintain an NP pressure and AF stress similar to the intact intervertebral disc. This patch had the lowest risk of complications and produced the greatest restorative effect of all patches simulated in this study.